Pattern Of Vocabulary Size Development - Yulianus P Mangewa (AgroSainT, 2013)
This mini project assessed students’ vocabulary size development. This an exploratory study aims at describe the developing of the number of word family the students know. The multiple-choice format from the Vocabulary Levels Test was used to collect the data namely 2000 version of the Vocabulary Size Test (VST). This mini project was particularly interested to know the students’ vocabulary size development. The findings revealed that the students’ vocabulary size was less than 2,000 word-families. This means that the vocabulary size of the students is still far from the standard required. This means that the students' vocabulary size is still far from the required standard. The majority of students do not have the English vocabulary size sufficiently to be used as a media to learn the subjects at university, though formal exposure to language has been given for more than 12 years. This paper, also explains the development of vocabulary size from first year(Semester Two) to fourth year (Semester Eight) at university.